2021
DOI: 10.1111/1759-7714.14067
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of lung cancer patients to COVID‐19: A review of the pandemic data from multiple nationalities

Abstract: Several studies have highlighted that cancer patients tend to be more susceptible to develop severe infection and to die from COVID‐19. Certain medical conditions such as immunosuppression, presence of comorbidities, and underlying pulmonary damage are possible determinants of disease severity, especially in lung cancer patients. While recent studies have shown that lung cancer is one of the most prevalent tumor types among COVID‐19 cancer patients, we still have an incomplete view of how data from several cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Lung cancer patients are exceptionally vulnerable compared with those with other cancer types when outbreaks of respiratory viruses occur because their damaged respiratory epithelium probably accelerates the invasion of virus into the lungs. [96] Approximately 80.0% of primary lung cancer cases worldwide are caused by smoking [97] Structural lung damage and reduced lung function caused by smoking, and lung damage caused by lung cancer treatment (surgery and radiotherapy) leads to additionally severe symptoms and consequences of SARS-CoV-2 infection in patients with lung cancer compared with other malignant solid tumors. [98] Therefore, the mortality rate of lung cancer patients with COVID-19 is higher than that of other malignant solid tumor patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer patients are exceptionally vulnerable compared with those with other cancer types when outbreaks of respiratory viruses occur because their damaged respiratory epithelium probably accelerates the invasion of virus into the lungs. [96] Approximately 80.0% of primary lung cancer cases worldwide are caused by smoking [97] Structural lung damage and reduced lung function caused by smoking, and lung damage caused by lung cancer treatment (surgery and radiotherapy) leads to additionally severe symptoms and consequences of SARS-CoV-2 infection in patients with lung cancer compared with other malignant solid tumors. [98] Therefore, the mortality rate of lung cancer patients with COVID-19 is higher than that of other malignant solid tumor patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of solid tumor immunosuppression results, in the majority of cases, oncological treatments are administered. Studies previously published that aimed to characterize the oncological population with COVID-19 found that lung cancer was one of the most prevalent subtypes [ 11 , 12 , 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In our study, which only included patients admitted to the ICU, the most common tumors were breast cancer, male genital tract cancer and urinary tract cancer.…”
Section: Discussionmentioning
confidence: 99%
“…В конце 2019 г. новая коронавирусная инфекция молниеносно распространилась по миру, вызвала более 105 миллионов случаев заболевания и более 2,3 миллиона смертей [1]. Разрушение клеток легких, вызванное инфекцией COVID-19, запускает локальный иммунный ответ, рекрутируя макрофаги и моноциты, высвобождая хемокины и провоспалительные цитокины, тем самым запуская адаптивные иммунные ответы Т-и В-лимфоцитов [2]. У большинства пациентов с COVID-19 рекрутированные клетки очищают легкие от инфекции, затем иммунный ответ снижается, и больные переносят заболевание бессимптомно или в легкой форме, не требующей госпитализации.…”
Section: Introductionunclassified